Public-private partnership in the social sphere - Kazbekov, T.B.; Romanko Е.B.; Mussabekova А.О.; Doskaliyeva, B.B. (BUKETOV BUSINESS REVIEW, 2017)
The article describes the prerequisites for the implementation of public-private partnership in Kazakhstan; a modern system of public-private partnership, the activities of JSC "Kazakhstan Public-Private Partnership" form of public-private partnership in Kazakhstan, the form of participation of countries, public-private partnership in the social sphere. Consider: the proposed approach for the social sphere; PPP models used in foreign countries, unresolved legal issues in Kazakhstan; the main obstacles to the development of the concession mechanism in the social sphere; the task of raising the profile of PPPs in the social sphere; the need of the Republic of Kazakhstan in PPP projects in the social sphere; The program is to provide children with preschool education and training "Balapan" for 2010-2020; implementation of PPP projects in health and education in Kazakhstan and Karaganda region; implementation of the project "Technology transfer and institutional reform in the health sector of the Republic of Kazakhstan"; the use of PPPs in health care in accordance with the "Salamatty Kazakhstan" state program of development of health; the results of the SWOT-analysis of PPP development in the social sphere of Kazakhstan; the achievement of goals by performing cash problems. It is concluded that the development of PPP in Kazakhstan has all the prerequisites; PPP mechanism is applied in industries related to the field of theory of state responsibility; Kazakhstan’s social sector needs to modernize and make it possible only with the participation of big business in close partnership with public authorities; further development of the economy of our state is impossible without a well-developed infrastructure and improve services to the population. The estimation of PPPs in the social sphere, implemented PPP projects in the Karaganda region. Summarizes the results of a public-private partnership in the social sphere. The implementation of public-private partnership in social sphere allows to attract private businesses to improve services in health and education.